2021
DOI: 10.3390/cancers13215532
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to Mesenchymal Transition: Key Regulator of Pancreatic Ductal Adenocarcinoma Progression and Chemoresistance

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest malignancies, characterized by aggressive biological behavior and a lack of response to currently available chemotherapy. Emerging evidence has identified epithelial to mesenchymal transition (EMT) as a key driver of PDAC progression and a central regulator in the development of drug resistance. EMT is a reversible transdifferentiation process controlled by complex interactions between multiple signaling pathways such as TGFb, Wnt, and Notch, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 200 publications
(227 reference statements)
0
37
0
8
Order By: Relevance
“…Studies have shown that ER stress plays a crucial role in activation of hepatic stellate cells [ 114 , 115 ] and that blocking the IRE1α–XBP1 pathway can significantly reduce liver fibrosis and tumor burden in several animal models for cirrhosis [ 47 ] and HCC [ 22 ]. Jia et al sought to provide a deeper investigation regarding the involvement of CAFs in epithelial–mesenchymal transition (EMT) in HCC [ 116 ], a process that is known to contribute to drug resistance in HCC and many other solid tumors [ 117 , 118 ]. Proteomic analyses identified that transglutaminase 2 (TG2) is substantially overexpressed in HCC cells that have obtained an EMT phenotype.…”
Section: Role Of the Tumor Microenvironmentmentioning
confidence: 99%
“…Studies have shown that ER stress plays a crucial role in activation of hepatic stellate cells [ 114 , 115 ] and that blocking the IRE1α–XBP1 pathway can significantly reduce liver fibrosis and tumor burden in several animal models for cirrhosis [ 47 ] and HCC [ 22 ]. Jia et al sought to provide a deeper investigation regarding the involvement of CAFs in epithelial–mesenchymal transition (EMT) in HCC [ 116 ], a process that is known to contribute to drug resistance in HCC and many other solid tumors [ 117 , 118 ]. Proteomic analyses identified that transglutaminase 2 (TG2) is substantially overexpressed in HCC cells that have obtained an EMT phenotype.…”
Section: Role Of the Tumor Microenvironmentmentioning
confidence: 99%
“…There have been some reports that several genes related to EMT in PDAC, including forkhead box protein M1 ( FOXM1 ), matrix metalloproteinase-1 ( MMP1 ), and vascular endothelial growth factor C ( VEGFC ), are targets for the treatment of PDAC. For example, the acquisition of EMT in PDAC is strongly associated with the expression of FOXM1 , which functions as a regulator of Snail and stimulates EMT [ 38 ]. A recent study reported that MMP1 promotes the metastasis of PC and that the inhibitory regulation of MMP1 with endogenous microRNA can attenuate the metastatic ability of pancreatic cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the close contact with DS suggests that in PDAC, these cells could be more easily released into the circulation in groups or individually. 36 , 63 , 64 This is the first study to jointly assess the expression of two epithelial markers (pan-cytokeratin and EPCAM) and one mesenchymal marker (vimentin) by immunohistochemistry in PDAC and to report the association between high expression of vimentin with advanced clinical stage (III and IV). This dual interaction could explain why these types of tumors are more aggressive at advanced stages.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a reversible transdifferentiation process controlled by complex interactions between multiple signaling pathways such as TGFb, Wnt, and Notch, which converge to a network of specific transcription factors that convert cancer cells of epithelial differentiation into a more mesenchymal phenotypic state. 36 The expression of mesenchymal markers favors the development of an invasive phenotype in which the tumor cell increases its migration, 20 as shown in both in vitro 21 , 37 and in vivo 20 , 31 models. In fact, it has been shown that Tβ 4 a peptide that regulate actin polymerization is predominantly expressed at the invasion front in colorectal tumor cells undergoing EMT, which suggest a role for Tβ 4 in invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%